METHODS OF RECEIVING OF PROTEINACEOUS PRODUCTS FROM PLANT RAW MATERIALS - Савчук, Ю. Ю.; Усатюк, С. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
This article is devoted to studying of the existing methods of production of proteinaceous products from plant raw materials. The solution of the problem connected with the shortage of protein in a modern diet of the person due usage of proteins of a phytogenesis is proposed. The article presents the analysis of the developed proteinaceous products using nonconventional plant sources of protein. The most commonly used raw materials for receiving proteinaceous products of plant origin are considered. Based on the analytical review of the literature; it is suggested the recipes of balanced products and reasonable technological parameters of their production. Advantages and shortcomings of the considered methods of receiving plant proteinaceous products are given.The own technology production of proteinaceous drink from raw materials widespread in Ukraine is offered.